Multi-scale fallow land dynamics in a water-scarce basin of the U.S. Southwest. Issue 3 (4th May 2021) - Plassin, Sophie; Koch, Jennifer; Wilson, Madison; Neal, Kevin; Friedman, Jack R.; Paladino, Stephanie; Worden, James
ABSTRACT: Improving our understanding of land-use change is critical for water management in semi-arid areas, due to its effects on the hydrological cycle. In the U.S. Southwest, fallowing farmland has become one strategy to reduce water use. Previous to this study, the magnitude and location of changes in fallowing have not been studied in depth. Using the 30-meter Cropland Data Layer, this study assessed the spatial and temporal patterns of fallowing in the U.S. portion of the Rio Grande/Río Bravo Basin (RGB) at three spatial scales (basin, state, and ecoregion) between 2008 and 2018. Our results do not show evidence of an increasing trend in fallowing at the basin level. However, the spatio-temporal patterns differed considerably among states and ecoregions, revealing hotspots of fallowing. By showing that land fallowing is not a widespread practice across the basin, our findings indicate that the potential of this strategy to save water has been underused.